Brazilian urban geography: from a diachronic analysis to the most cited works in the last decade - Eustogio Wanderley Correia Dantas; José Borzacchiello da Silva (Confins)
In the field of contemporary Brazilian geography, it is urgent to continue studies on the city and the urban. This article is an approach by the investigation of the material in question, since the beginning, a classic bibliography, facilitated by the existence of tools based on the information technology. In addition to the indication of the work, it deals with the volume of quotations relating to it. The use of studies based on the H index will allow the updating of the studies with the presentation of the persons responsible for the production of important works on the urban geography in Brazil, thus making it possible to spatialize the production in the country (volume of citations